Spatially confined system interacting with Yukawa potential - Holovko, M.F.; Kravtsiv, I.Y.; Soviak, E.M. (Condensed Matter Physics, 2009)
Hard wall confined fluid with Yukawa potential of interaction is considered. A solution of the inhomogeneous
Ornstein-Zernike equation for the pair correlation function is obtained. The expression for the particle density
profile is found by the method of functional differentiation of Helmholtz free energy with respect to the external
field. The contribution to the behavior of particle density near the surface comes from the initial potential
as well as from the collective screening interaction effects. It is shown that the contact value of the profile
satisfies the condition of the contact theorem. Dependence of the adsorption coefficient on the particle density
is calculated. It is also shown that in the case of repulsive Yukawa interaction the sign of the adsorption
coefficient changes with the increase of the particle density. Розглянуто обмежений твердою стiнкою плин з потенцiалом взаємодiї Юкави. Отримано розв’язок просторово неоднорiдного рiвняння Орнштейна-Цернiке для парної кореляцiйної функцiї. Методом функцiонального диференцiювання вiльної енергiї за зовнiшнiм полем знайдено вираз для профiлю густини частинок. Показано, що вклад у поведiнку густини частинок поблизу поверхнi вносить як вихiдний потенцiал, так i колективнi ефекти екранування взаємодiї. Розраховано залежнiсть коефiцiєнта адсорбцiї вiд густини числа частинок. Показано, що у випадку притягувальної взаємодiї iз збiльшенням густини числа частинок системи змiнюється знак коефiцiєнта адсорбцiї.